Low-operating temperature resistive nanostructured hydrogen sensors. (8th October 2019) - Hashtroudi, H.; Atkin, P.; Mackinnon, I.D.R.; Shafiei, M.
Abstract: With increasing attention on hydrogen (H2 ) produced by renewable energy methods for transport and other applications, an updated evaluation of H2 monitoring techniques is timely. The emergence of nanomaterials with unique properties enables a new class of H2 sensing materials, exhibiting important attributes such as high surface area to volume ratio, reactivity and number of active sites. The development of these materials allows for improved H2 sensing methods with increased sensitivity, selectivity, speed and improved economy for both financial cost and power consumption. These advances enable small-scale, high-performance H2 sensors for use in emerging hybrid renewable energy systems, including Internet of Things (IoT) or mobile systems. While literature reports on H2 sensors include thermal conductivity, resistive, optical, acoustic, electrochemical and catalytic methods, this review will focus on resistive H2 sensing nanomaterials. Three classes of these nanomaterials are discussed: metal oxides, transition metal dichalcogenides, and graphene based nanomaterials. As a key aim of this review is improved economy of use, we will elaborate only sensors operating at temperatures lower than 200 °C, with a focus on potential for room temperature operation. Highlights: Survey of resistive nanostructured H2 sensors at low operating temperature. Key materials are metal oxides, transition metal dichalcogenides and graphene. H2 sensing properties of nanomaterials are prospective with systematic evaluations.